Synthesis of next-generation silicon/graphite anode materials via molten salt-assisted magnesiothermic reduction for lithium-ion batteries - Fedakar, Burak (Graduate School, 2023)
Silicon has emerged as a promising anode material for Li-ion batteries due to several advantages it offers. One of the key advantages is its high energy density. With a theoretical specific capacity of 4200 mAh/g, silicon can store a considerably larger amount of lithium ions compared to traditional graphite anodes, which have a specific capacity of 372 mAh/g. This higher capacity translates into increased energy storage capabilities, allowing for longer battery life and enhanced performance in various applications. Another advantage of silicon anodes is their improved charge/discharge efficiency. Silicon exhibits a lower operating potential compared to graphite, resulting in reduced polarization and enhanced electrochemical performance. This characteristic enables faster charging and discharging rates, making silicon-based Li-ion batteries suitable for high-power applications such as electric vehicles (EVs) and portable electronics. Furthermore, silicon anodes offer the potential for better environmental sustainability. Silicon is abundantly available in the Earth's crust, making it a more accessible and potentially cost-effective material for large-scale battery production. Additionally, the use of silicon anodes can contribute to reducing greenhouse gas emissions by facilitating the adoption of clean energy technologies and reducing dependence on fossil fuels. However, it is important to consider the drawbacks associated with silicon anode materials. One significant challenge is the issue of volume expansion and contraction during lithium insertion and extraction. Silicon undergoes a significant volume expansion of approximately 300% when fully lithiated, leading to mechanical stress, electrode degradation, and capacity fading over repeated cycles. This phenomenon, known as the "silicon anode swelling problem," poses a major obstacle in commercializing silicon-based Li-ion batteries. To address this issue, extensive research is being conducted on various approaches such as nanostructuring silicon, incorporating carbon-based materials, and using silicon composites or alloys to mitigate the volume expansion problem and improve the cycling stability of silicon anodes. In terms of the production of silicon, one method of synthesis is magnesiothermic reduction (MTR). This process involves the reaction between silica (SiO2) and magnesium (Mg) at high temperatures to produce nanosilicon. Magnesium acts as a reducing agent, reacting with silica to form silicon and magnesium oxide (MgO) as a by-product. The resulting silicon can then be further processed and utilized as an anode material in Li-ion batteries. In conclusion, silicon anode materials offer significant advantages for Li-ion batteries, including high energy density, improved charge/discharge efficiency, and potential environmental sustainability. However, challenges related to volume expansion and cycling stability need to be overcome. The production of silicon through magnesiothermic reduction provides a viable method for obtaining silicon for battery applications, but further research and development are required to optimize the material properties and address the remaining challenges. In this study, silicon anode materials for lithium-ion batteries were synthesized and characterized. First, silica particles were synthesized according to the Stöber method. Then, two different reaction pathways were followed for the magnesiothermic reduction of silica. In one crucible, magnesium and silica were added with a mole ratio of 2:1 respectively, while in the other crucible, CaCI2 was also added with a mole ratio of 1:5 for silica. After a 6h reaction time, the yielded products were analyzed by XRD spectroscopy. The XRD result of the product synthesized without CaCl2 clearly indicated the presence of a well-defined Mg2Si crystal structure, while the same structure was not observed in the product synthesized in the presence of CaCI2. This output suggested that the presence of CaCl2 in the synthesis process has a significant influence on the product composition and concluded that side reactions are not favorable in the presence of molten salt. Furthermore, the XRD results did not show any remaining silica particles, as the addition of a 5% excess of Mg facilitated the complete reduction of silica particles. Then acid washing was accomplished for both products to remove undesirable by- products. Following, the pure silicon active materials were subjected to XRD, BET, and SEM analyses. In addition, the utilization of a heat scavenger resulted in variations in both surface properties and particle and crystallite size. It was observed that using CaCI2 was a practical idea to hinder the agglomeration of the silicon product. The crystallite size of the silicon active material synthesized in the presence of CaCl2 was found to be 16 nm, while the other material measured 27 nm. These differences were complemented by BET results, which revealed that the molten-salt-assisted silicon exhibited a notably higher specific surface area (158.791 m2/g.) compared to the other silicon sample (63.060 m2/g.). These results were attributed to the excessive heat during the exothermic reduction being absorbed by CaCI2. To assess the electrochemical performance of synthesized silicon active materials, silicon-graphite anodes and commercial graphite anode were prepared. These anodes were designed to examine materials synthesized both in the presence and absence of CaCl2. The charge and discharge analyzes of three lithium coin cells were performed. The lithium cell prepared from the silicon material synthesized via molten salt-assisted process exhibited a first discharge capacity of 470.236 mAhg-1 at 20 mA, while the other silicon-graphite cell displayed a first discharge capacity of 429.679 mAhg-1. However, after 50 cycles conducted at 50 mA, specific capacities decreased to 322.675 mAhg-1 and 289.253 mAhg-1, respectively. These results revealed that molten salt-assisted magnesiothermic reduction process is a efficient method to synthesis the next generation silicon nanoparticles
Lityum iyon piller için erimiş tuz yardımlı magnezyotermik indirgeme yoluyla yeni nesil silisyum- grafit anot malzemelerinin sentezi
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2023
Keywords: Lithium-ion batteries; Lityum iyon piller; Graphite anode materials; Grafit anot malzemeler; Magnesium; Magnezyum; Silicon; Silisyum